Perinatal tuberculosis—An approach to an under-recognized diagnosis - Schaaf, H. Simon; Bekker, Adrie; Rabie, Helena (Frontiers in Public Health, 2023)
Tuberculosis (TB) in young infants (<3 months of age), often referred to as perinatal TB, is under-diagnosed leading to severe morbidity and high mortality. Perinatal TB includes both congenital and postnatal transmission of Mycobacterium tuberculosis. We aim to increase awareness of TB in neonates and young infants and to provide guidance on assessment and management when in contact with mothers with TB during or soon after pregnancy. Approximately 217,000 pregnant women develop TB annually; if they are not diagnosed and treated during pregnancy, their infants are at high risk of adverse birth outcomes and TB disease. Although safe and effective antituberculosis treatment regimens are available in pregnancy, the diagnosis of TB is challenging. Infants born to mothers newly diagnosed with TB, not on effective treatment or with cultures not yet negative should be assessed for TB disease or M. tuberculosis infection. TB preventive therapy should be instituted if the infant is clinically well but exposed to TB, while prompt initiation of TB treatment is essential if TB disease is presumed. HIV status of mother and infant should be considered, as this will affect management. Further research is needed for diagnosis and prevention of TB during pregnancy, early diagnosis of TB in infants and antituberculosis drug pharmacokinetics in young infants.